SIGHAT TA’LIQ PERNIKAHAN DALAM PENYELESAIAN KONFLIK RUMAH TANGGA DI DESA LOLO HILIR KECAMATAN BUKIT KERMAN PERSPEKTIF KOMPILASI HUKUM ISLAM (KHI) DI INDONESIA - Ningsih, Annisa Sri Ayu (Fakultas Syariah (Syari'ah Faculty ), 2024)
This research examines the role of Sighat Ta’liq in resolving domestic conflicts in Lolo Hilir Village, Bukit Kerman Sub-district from the perspective of the Compilation of Islamic Law (KHI) in Indonesia. The research findings reveal that the factors that cause violations of Sighat Ta’liq in the village include husbands who leave their wives, do not provide mandatory maintenance, hurt their wives, and leave their wives in trouble. The reasons for divorce submitted by informants who violate Sighat Ta’liq vary, with one of the main causes being a lack of education about marriage, which can trigger conflicts related to the violation. Nevertheless, many residents who committed the offence did not apply for divorce in court, citing financial constraints, long distances, and ignorance of court procedures and Sighat Ta’liq. The resolution of domestic conflicts in this village is mostly done through marriage guidance by penghulu and religious extension workers, which involves individual and group counselling approaches, as well as religious counselling to the community. The method used in this research is normative empirical, which combines normative legal analysis with empirical data obtained in the field. This study concludes that an increased understanding of the Sighat Ta’liq and marriage education is essential to prevent violations and resolve household conflicts effectively.